2015
DOI: 10.4067/s0301-732x2015000200012
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic imaging of the brain of normal neonatal foals

Abstract: RESUMENEl objetivo de este estudio fue proporcionar una descripción detallada de la anatomía normal del cerebro de potrillos neonatos y de las estructuras asociadas mediante tomografía computarizada (TC) y cortes anatómicos. Se utilizó un escáner de cuarta generación y se adquirieron imágenes transversales con un grosor de dos milímetros. Tras el estudio por TC, los animales fueron sacrificados por razones no relacionadas con patologías de la cabeza. Para ayudar en la identificación precisa del cerebro y las e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Computed tomography (CT) has become an important imaging modality for the diagnosis of diverse head disorders in the horse [16]. The cross-sectional imaging modality provides images of nasal and paranasal passages, the teeth, skull bones, the hyoid apparatus, and the teeth without superimposition and allows 3-dimensional reconstruction [7].…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) has become an important imaging modality for the diagnosis of diverse head disorders in the horse [16]. The cross-sectional imaging modality provides images of nasal and paranasal passages, the teeth, skull bones, the hyoid apparatus, and the teeth without superimposition and allows 3-dimensional reconstruction [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of contrasted techniques may be an important adjunct to anatomical studies through imaging diagnostics because they offer more advantages when used in living animals; they present greater dispersion due to the pressure and flow of the active vessels [10,22]. In the present study, contrast solubility contributed to dispersion as well as the administration of a large volume that was ten-fold higher than the dose indicated for use in living animals (2 mL/kg), even without active vascularization or gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of an image diagnostic for anatomical studies in preserved organisms must take into account the structures or organs to be explored, the preservation method, the protocols and equipment to be used, the operator's ability, and the techniques and parameters that can contribute to the formation of the images [22,31].…”
Section: Discussionmentioning
confidence: 99%
“…Parallel with Cabreraa et al (2015), the CT images of the brain and associated structures of normal neonatal foals provided excellent detail of clinical anatomy. Previous studies reported the normal anatomy of the equine head showed similar results with CT images (Arencibia et al, 2000;Smallwood et al, 2002;De Zani et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…9(3): 230-240. www.wvj.science-line.com medicine are designed for human patients. Hence, these machines are only suitable for small-sized animals such as donkeys (Cabreraa et al, 2015). P40 and CT carrels are available for the learning of neuroanatomy and describing the most complex parts of the nervous system such as the brain.…”
Section: Introductionmentioning
confidence: 99%